Peripheral nerve injury increases glutamate-evoked calcium mobilization in adult spinal cord neurons - Doolen Suzanne; Blake Camille B; Smith Bret N; Taylor Bradley K (SAGE Publishing, 2012)
Abstract Background Central sensitization in the spinal cord requires glutamate receptor activation and intracellular Ca2+ mobilization. We used Fura-2 AM bulk loading of mouse slices together with wide-field Ca2+ imaging to measure glutamate-evoked increases in extracellular Ca2+ to test the hypotheses that: 1. Exogenous application of glutamate causes Ca2+ mobilization in a preponderance of dorsal horn neurons within spinal cord slices taken from adult mice; 2. Glutamate-evoked Ca2+ mobilization is associated with spontaneous and/or evoked action potentials; 3. Glutamate acts at glutamate receptor subtypes to evoked Ca2+ transients; and 4. The magnitude of glutamate-evoked Ca2+ responses increases in the setting of peripheral neuropathic pain. Results Bath-applied glutamate robustly increased [Ca2+]i in 14.4 ± 2.6 cells per dorsal horn within a 440 x 330 um field-of-view, with an average time-to-peak of 27 s and decay of 112 s. Repeated application produced sequential responses of similar magnitude, indicating the absence of sensitization, desensitization or tachyphylaxis. Ca2+ transients were glutamate concentration-dependent with a Kd = 0.64 mM. Ca2+ responses predominantly occurred on neurons since: 1) Over 95% of glutamate-responsive cells did not label with the astrocyte marker, SR-101; 2) 62% of fura-2 AM loaded cells exhibited spontaneous action potentials; 3) 75% of cells that responded to locally-applied glutamate with a rise in [Ca2+]i also showed a significant increase in AP frequency upon a subsequent glutamate exposure; 4) In experiments using simultaneous on-cell recordings and Ca2+ imaging, glutamate elicited a Ca2+ response and an increase in AP frequency. AMPA/kainate (CNQX)- and AMPA (GYKI 52466)-selective receptor antagonists significantly attenuated glutamate-evoked increases in [Ca2+]i, while NMDA (AP-5), kainate (UBP-301) and class I mGluRs (AIDA) did not. Compared to sham controls, peripheral nerve injury significantly decreased mechanical paw withdrawal threshold and increased glutamate-evoked Ca2+ signals. Conclusions Bulk-loading fura-2 AM into spinal cord slices is a successful means for determining glutamate-evoked Ca2+ mobilization in naïve adult dorsal horn neurons. AMPA receptors mediate the majority of these responses. Peripheral neuropathic injury potentiates Ca2+ signaling in dorsal horn.